(untitled) (Bangladesh Journal of Bioethics, 2016)
Correction: On 10th January 2017 the first author’s name was changed from Gabriel Vidal Vidal Quiñones TO Gabriel Vidal Quiñones on the website. The PDF was correct. The advent of the technological era put us in a radically different position against nature, because the whole biosphere can now be affected by our actions. Therefore, even though non-humans always had moral significance, only recently we start to realize their importance. So, we recognize them as morally significant much more than before. This brings a renewal to, and makes more patent than ever, the discussion over vegetarianism, since it challenges our view on the relation between human beings and other sentient beings. In Utilitarianism and Vegetarianism, Peter Singer tries to answer the question through the conceptual resources of utilitarianism. In contrast, we shall try to show that the issue of vegetarianism can start to be solved better in an ethical consideration that transcends the merely prescriptive.